2017
DOI: 10.1080/10408398.2016.1169157
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous chlorine dioxide treatment of horticultural produce: Effects on microbial safety and produce quality–A review

Abstract: Microbial load on fresh fruit and vegetables causes decay and losses after harvest and may lead to foodborne illness in case of contamination with human pathogens on raw consumed produces. Washing with tap water only marginally reduces microorganisms attached to produce surfaces. Chlorine is widely used for decontamination on fresh horticultural produces. However, due to harmful by-products and the questionable efficacy it has become increasingly challenged. During the last 20 years, the interest to study ClO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 87 publications
0
64
0
Order By: Relevance
“…The application of 20,000-ppm calcium hypochlorite is likely the most commonly used chemical treatment. However, although recommended by the Food and Drug Administration (FDA), this method carries distinct drawbacks concerning worker safety and environmental impact, difficulty to make organic food claims, disinfection efficacy that may vary in relation to the physical properties of the seed surface (e.g., smooth vs scarified) [128,130], and impact on product quality [138]. Consequently, there is a need for alternative methods that optimally combine disinfection efficacy with safety and environment-friendly features.…”
Section: Microbiological Safety Of Sprouts and Microgreensmentioning
confidence: 99%
“…The application of 20,000-ppm calcium hypochlorite is likely the most commonly used chemical treatment. However, although recommended by the Food and Drug Administration (FDA), this method carries distinct drawbacks concerning worker safety and environmental impact, difficulty to make organic food claims, disinfection efficacy that may vary in relation to the physical properties of the seed surface (e.g., smooth vs scarified) [128,130], and impact on product quality [138]. Consequently, there is a need for alternative methods that optimally combine disinfection efficacy with safety and environment-friendly features.…”
Section: Microbiological Safety Of Sprouts and Microgreensmentioning
confidence: 99%
“…Additionally, chlorinated washes lack efficacy outside a narrow pH range and can potentially form carcinogenic substances, such as trichloramines, as byproducts of treatment (Richardson et al, 1998;Shen et al, 2016). The use of chlorine dioxide (ClO 2 ) washes as an alternative to conventional chlorinated washes has increased in popularity over the past 20 years due to their high oxidative capacity, stability over a wide pH range, antimicrobial efficacy, and limited toxic byproduct formation (Gómez-López et al, 2009;Wu, 2016;Bridges and Wu, 2018;Praeger et al, 2018;Tadepalli et al, 2018;Sun et al, 2019). Currently, ClO 2 is used for applications such as disinfection of drinking water and wastewater, antimicrobial agent in water used in poultry processing and fruits and vegetables that are not raw agricultural commodities, sterilization of medical surfaces, equipment, and waste, and bleaching in pulp and paper industries (Gómez-López et al, 2009;Praeger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, control presented the lowest firmness among all the groups since day 2, which demonstrated that the firmness of strawberries packed in 6 g/L NaClO 2 , and 9 g/L NaClO 2 was better maintained by ClO 2 treatment. The delayed softening of fruit by ClO 2 treatment has been widely reported [3], which was mainly related to the reduced metabolism and inhibited activities of enzymes.…”
Section: Surface Colormentioning
confidence: 97%